Arbovirus circulation among febrile patients at the greater Accra Regional Hospital, Ghana - Simon Kofi Manu; Joseph Humphrey Kofi Bonney; Deborah Pratt; Farida Njelba Abdulai; Eudosia Esinam Agbosu; Prince Osei Frimpong; Theophilus Korku Adiku (BMC Research Notes, 2019)
Abstract Objective Arboviruses, Dengue and Chikungunya have become major international public health concerns due to their epidemics and introduction in new areas. In Ghana, little is known is about Dengue and Chikungunya viruses though the country has been listed as part of the 34 countries in which the viruses are endemic. This has been attributed partly to the lack of diagnostic tools for these viruses in several health facilities and institutions across the country. The purpose of this study was to detect and characterize these viral pathogens among febrile patients in Accra Ghana. Results This hospital-based cross-sectional study enrolled 260 suspected Dengue and/or Chikungunya febrile patients who submitted their clinical specimens of serum. Out of the total number tested with both molecular and serological tools, Chikungunya and Dengue specific total antibodies were detected from 72 (27.69%) and 180 (69.23%) respectively. None of the participants tested positive for Dengue and Chikungunya by reverse transcription-polymerase chain reaction (RT-PCR) and with the Dengue-specific NS1 antigen strip kits. Our findings suggested that Dengue and Chikungunya viruses may be circulating but are being missed among febrile patients. Differential diagnosis work-up in febrile patients should be made to include Dengue and Chikungunya infections.